Comparative research on three types of MIL-101(Cr)-SO3H for esterification of cyclohexene with formic acid. Issue 10 (15th February 2019) - Ma, Lijuan; Xu, Luo; Jiang, Haoran; Yuan, Xia
Abstract : MIL-101(Cr)-SO3 H was prepared with three different mineralizers, namely HCl, HF and NaAC, respectively. And catalytic performance and stability of three samples catalyzing the esterification of cyclohexene with formic acid were compared. Abstract : MIL-101(Cr)-SO3 H was prepared by a one-pot synthesis method using CrO3 or Cr(NO3 )3 · 9H2 O as a Cr source and 2-sulfoterephthalic acid monosodium salt as a ligand with three different mineralizers, HCl, HF and NaAC, respectively. Among the prepared catalysts, MIL-101(Cr)-SO3 H, which uses HCl as a mineralizer, has a high specific surface area and the strongest acidity compared with the other two mineralizers. When these catalysts were used to catalyze the esterification of cyclohexene with formic acid, MIL-101(Cr)-SO3 H prepared using HCl as a mineralizer possessed the highest catalytic activity in the esterification, because the conversion rate of cyclohexene is 63.97%, whereas MIL-101(Cr)-SO3 H prepared using NaAC and HF as a mineralizer shows cyclohexene conversion rates of 38.40% and 32.46%, while their selectivity to cyclohexyl formate is about 97.50%. MIL-101(Cr)-SO3 H with HCl as a mineralizer can be reused three times in succession without any loss of catalytic activity.